Ilmu Falak dalam Perspektif Filsafat Ilmu - Alwi, Bashori; Muslifah, Siti; Zainuri, Mursyid (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study discusses the integration of astronomy with the philosophy of science as an effort to position astronomy not only as a technical discipline, but also as a science with profound ontological, epistemological, and axiological dimensions. Astronomy, with its objects of study being celestial bodies and their regularities, is integrated with philosophical values to ensure the validity of its calculation (hisab) and observation (rukyat) methods and its practical benefits for Muslims. Several problems, such as uncertainty about the nature of the objects of astronomy, epistemological conflicts between the hisab and rukyat methods, differences in determining the beginning of the Hijri month, and several other problems, all disrupt social order and create disharmony in community worship. This research is a library study whose data is primarily drawn from books and various scientific literature such as articles. Furthermore, all findings are analyzed and concluded qualitatively. Through a philosophical approach, astronomy can be developed critically, reflectively, and adaptively to the development of modern technology. This integration is expected to strengthen the holistic paradigm of Islamic science, bridge science and spiritual values, and encourage the creation of orderly and harmonious religious practices. The results of this study will form the basis for education, research, and policies for determining a more scientific and beneficial Hijri calendar.